Estudio contrastivo del género discursivo del ensayo argumentativo - Moore, Pauline; Andrade Mayer, Hugo Abelardo (Colombian Applied Linguistics Journal, 2016)
Discourse genres can vary from one culture to another (Connor, 2003) and studies suggest that second language users tend to transfer patterns from one language to the other (Upton and Connor, 2001; Woolever, 2001). However, we know relatively little about how the highly valued genre of the academic essay is learned. In order to identify generic models used by Mexican university students in argumentative essays, we analyzed 36 exemplar texts produced by 18 students in Spanish and English as a second language. We analyzed the essay thesis and reiteration using appraisal theory (Martin and White, 2005; Martin and Rose, 2007) to classify these segments into the categories open and closed with reference to the language of appraisal used in these textual segments. In appraisal theory, argumentation patterns in which monoglossic language choices predominate close down the possibilities for argument, whereas heteroglossic patterns open up the opportunity for disagreement and, hence, argumentation. This resulted in us being able to assign the category of closed or open to the thesis and reiteration. We used these categories to characterize five generic structures: 1) closed thesis, reiteration in conclusion; 2) open thesis, closed reiteration; 3) closed thesis, open reiteration; 4) open thesis, no position assumed; 5) closed thesis in conclusion. We found a preference for the generic structure 2, ‘open thesis, closed reiteration’, which occurred in seven of the essays in Spanish and six in English. Notably, we observed a high degree of variability in the patterns used indicating a lack of agreement in this community with regard to the norm for generic structure.